2010
DOI: 10.1021/ac101714u
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Independent Porous Nanocontainers for Single-Molecule Fluorescence Studies

Abstract: In this work, we demonstrate the capability of using lipid vesicles biofunctionalized with protein channels to perform single molecule fluorescence measurements over a biologically relevant temperature range. Lipid vesicles can serve as an ideal nanocontainer for single molecule fluorescence measurements of bio-macromolecules. One serious limitation of the vesicle encapsulation method has been that the lipid membrane is practically impermeable to most ions and small molecules, limiting its application to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
14
1
Order By: Relevance
“…Addition of equal amounts of the protein α-hemolysin to membranes containing varying amounts of cholesterol (0–50 mol%) clearly demonstrated an increase in membrane conductance due to α-hemolysin. Although α-hemolysin is not classed as a member of the cholesterol-dependent-cytolysins, recent studies in the literature indicate cholesterol does impact upon its activity and membrane interactions [31], with depletion of cholesterol from membranes resulting in arrest in the assembly of the α-hemolysin [32]. In the current study however, the highest levels of membrane conductance due to α-hemolysin were observed in the sample containing no cholesterol in the membrane (Figure 1).…”
Section: Resultscontrasting
confidence: 60%
“…Addition of equal amounts of the protein α-hemolysin to membranes containing varying amounts of cholesterol (0–50 mol%) clearly demonstrated an increase in membrane conductance due to α-hemolysin. Although α-hemolysin is not classed as a member of the cholesterol-dependent-cytolysins, recent studies in the literature indicate cholesterol does impact upon its activity and membrane interactions [31], with depletion of cholesterol from membranes resulting in arrest in the assembly of the α-hemolysin [32]. In the current study however, the highest levels of membrane conductance due to α-hemolysin were observed in the sample containing no cholesterol in the membrane (Figure 1).…”
Section: Resultscontrasting
confidence: 60%
“…The G-quadruplex has also been studied using other single-molecule methods, including fluorescence resonance energy transfer (FRET) spectroscopy [82,84,85,92], and atomic force microscopy (AFM) [93-95]. Unlike these single molecule approaches, the nanopore electrical detection is a label-free method and does not need the attachment of probing agents such as fluorophores or immobilization on solid surfaces for observation.…”
Section: Discussion Of Nanopore Technologymentioning
confidence: 99%
“…Most methods that seek to image individual molecules at higher fluorophore concentrations either increase the local protein concentration, or further confine the laser illumination volume. For example, the reaction volume can be reduced by encapsulating the biochemical reaction of interest in a porous lipid vesicle [41][42][43][44][45], within a PDMS nanochannel [46], or within a confined volume induced by a convex lens and a coverslip [47]. Alternatively, the laser excitation can be confined to an attoliter volume within a zero-mode waveguide [48][49][50], or near plasmonic nano-structures that locally enhance the light excitation [51,52].…”
Section: Breaking the Single-molecule Concentration Barriermentioning
confidence: 99%